Reposting Content in Social Media: An Ethical and Islamic Legal Review - Akhsan Ramdhani, Ahmad Thoriq (Jurnal Paradigma, 2024)
This study aims to identify and analyze Islamic principles relevant to the practice of reposting on social media. The main focus of this study is to assess the legal implications related to the dissemination of unverified or detrimental information, as well as to provide practical recommendations for social media users to be able to apply Islamic teachings in every digital interaction. The method used is the qualitative normative-Islamic legal method to analyze the practice of reposting content on social media from the perspective of Islamic ethics and law. Data were collected from various classical literature sources such as fiqh books, tafsir, and hadith and contemporary literature such as fatwas and academic articles. The results of the study indicate that repost content can allow users to spread information, images, videos, or opinions without creating original content, but in a way that allows the content to be seen by their own audience. In practice, several principles need to be considered, such as the truth of information and copyright protection. Islam also teaches to respect the property rights of others, including copyright of intellectual works, either in the form of attribution or permission before sharing the content on social media.